Gestión administrativa y su relación con las asignaciones presupuestaria con fuentes de financiamiento y ejecución en el distrito de salud 09d15 hospital El Empalme del cantón El Empalme, periodo 2012 - Mera González, Efrén Eugenio (2015)
This study aims to determine the influence of administrative management and its relation to budgetary allocations sources of financing and execution Health District Hospital 09D15 Canton El Empalme, during the period 2012. For realization it, were used methods such as: historical and logical, deductive and inductive analytic-synthetic. It was based on the information provided by the Health District Hospital 09D15 Canton El Empalme to find a conclusion. The planning with a coordinated budget are strategic tools for government financial management; any organizational structure should be planned in advance as well as the goals and objectives, so that any institution uninsured plans will fail. The most essential problems of the public administration structures are to be sure that the resources allocated by the national government are sufficient for operation and provision of services for which they were made. It has been observed the administration of the Health District hospital 09D15 El Empalme not have an adequate budget planning because it lacks a department to do this job. The administrative and financial departments are not aligned with the operations manual of the ministry of public health. This is very important to be reclassified. The department of human talent does not monitor procedures for Annual Operating Plan are met. With the results of the investigation we can conclude the level of compliance of the Annual Operating Plan (AOP) is high relative to assigned a 98.14% execution, while we appreciate over the previous period had a strong increase.